DAMPAK INTEGRASI EKONOMI TERHADAP INVESTASI DI KAWASAN ASEAN: ANALISIS MODEL GRAVITASI - Ridwan, Ridwan (LPPM Universitas Terbuka, 2009)
The objective of the study were to analyze the effect of ASEAN and NAFTA, EU, Cind (China-India) and Mercosur economic integration to investment activities in the nations of ASEAN area integration. The study used a gravity model with simultaneous equations and panel data with estimator Generalized Method of Moments (GMM). The result of the study was the economic integration of ASEAN has a positive effect to the increasing investment of the ASEAN nations. The NAFTA economic integration area has a higher investment fascination of the EU, Mercosur and Cind integration areas.